Prostaglandin EP Receptors Involved in Modulating Gastrointestinal Mucosal Integrity - Koji Takeuchi; Shinichi Kato; Kikuko Amagase (Elsevier, 2010)
Abstract.: Endogenous prostaglandins (PGs) play an important role in modulating the mucosal integrity and various functions of the gastrointestinal tract, and E type PGs are most effective in these actions. PGE2 protected against acid-reflux esophagitis and prevented the development of gastric damage induced by ethanol or indomethacin, the effects mimicked by EP1 agonists and attenuated by an EP1 antagonist. Adaptive cytoprotection induced by mild irritants was also attenuated by the EP1 antagonist. On the other hand, the acid-induced duodenal damage was prevented by EP3/EP4 agonists and worsened by EP3/EP4 antagonists. Similarly, the protective effect of PGE2 on indomethacin-induced small intestinal damage or DSS-induced colitis was mimicked by EP3/EP4 agonists or EP4 agonists, respectively. The mechanisms underlying these actions of PGE2 are related to inhibition of stomach contraction (EP1), stimulation of duodenal HCO3− secretion (EP3/EP4), inhibition of small intestinal contraction (EP4), and stimulation of mucus secretion (EP3/EP4) or down-regulation of cytokine secretion in the colon (EP4), respectively. PGE2 also showed a healing-promoting effect on gastric ulcers and intestinal lesions through the activation of EP4 receptors, the effect associated with stimulation of angiogenesis via an increase in VEGF expression. These findings should aid the development of new strategies for treatment of gastrointestinal diseases. Keywords:: prostaglandin E, EP receptor subtype, mucosal protection, function, gastrointestinal tract